Przekształć podane wyrażenia na sumy algebraiczne;
a) (a+2)(a-2)
b) (10x+1)(10x-1)
c) (4a-2b)(4a+2b)
d) ½t+3q)(½t-3q)
e) (2a²-0,1)(2a²+0,1)
f)(x+5)(5-x)
g)(3a+1)(1-3a)
h)(0,7-7x³)(7x³+0,7)
i)(x-¹/₃y²)(x+¹/₃y²)
j)(ab²+a²b)(ab²-a²b)

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-14T16:40:31+01:00
A)=a²-4
b)=100x²-1
c)=16a²-4b²
d)=1/4t²-9q²
e)=4a⁴-0,01
f)=-x²+25
g)=-9a²+1
h)=0,49-49x⁶
i)=x²-1/9y⁴
j)=a²b⁴-a⁴b²
8 2 8
2009-12-14T16:44:08+01:00
A) (a+2)(a-2)=a²-4
b) (10x+1)(10x-1)=100x²-1
c) (4a-2b)(4a+2b)=16a²-4b²
d) ½t+3q)(½t-3q)=1/4t²-9q²
e) (2a²-0,1)(2a²+0,1)=4a(potęga 4)-0,01
f)(x+5)(5-x)=x²-25
g)(3a+1)(1-3a)=9a²-1
h)(0,7-7x³)(7x³+0,7)=0,49-49x( do potegi 6 )
i)(x-¹/₃y²)(x+¹/₃y²)=x²-1/9y ( do potegi 4)
j)(ab²+a²b)(ab²-a²b)=ab(do pot. 4)-a(pot. 4 )b²
7 5 7